Can the carbon market protect the amazon?: estimating effects from Brazilian REDD+ projects - Correia, Marcos Paulo Rodrigues (2024)
This study investigates the impacts of REDD+ (Reducing Emissions from Deforestation and Forest Degradation) on vegetation conservation in the Brazilian Legal Amazon. Based on a novel dataset covering virtually all carbon projects in the country from 2000 to 2022, and employing synthetic control methods along with estimates of predictive errors as Cattaneo et al. (2022b) and Cattaneo et al. (2021), this research aimed to quantify the unit time effect and the average treatment effect on the treated (ATT), to understand the impact of these projects. Contrary to the expected results of REDD+ initiatives, our conclusions reveal a lack of significant benefits in terms of preserving natural formations. Our results highlight critical considerations for the design and implementation of marketbased conservation mechanisms, pointing out key aspects to effectively leverage carbon finance for environmental preservation.